Clinical comparison of conventional suture and tissue adhesive in third molar surgeries: a systematic review - dos Santos, Aída Juliane Ferreira; Monteiro, João Luiz Gomes Carneiro; Moraes, Sandra Lúcia Dantas; Vasconcelos, Belmiro Cavalcanti do Egito; Pellizzer, Eduardo Piza [UNESP] (My University, 2023)
The use of cyanoacrylate tissue adhesive for surgical wound closure has become increasingly popular in recent years and has shown efficacy. Therefore, the aim of this systematic review was to compare the effectiveness of cyanoacrylate adhesive as a substitute for conventional suture placement after extraction of impacted third molars. The PubMed/MEDLINE, Scopus, Cochrane, and gray literature databases were searched for randomized or controlled prospective clinical trials published up to October 2022 that compared the use of cyanoacrylate adhesive and conventional silk suture in third molar surgeries. The risk of bias of each study was assessed using the RoB 2 tool (revised Cochrane risk of bias tool for randomized trials). Five randomized clinical trials with a total of 236 patients were included. The most commonly evaluated outcomes were pain and bleeding. The type of adhesive used varied and included ethyl-2-cyanoacrylate, isoamyl 2-cyanoacrylate, and a mixture of n-butyl cyanoacrylate and 2-octyl cyanoacrylate. Compared with 3-0 silk suture, cyanoacrylate tissue adhesive resulted in lower levels of postoperative pain in 3 studies and lower rates of bleeding in all 5 studies. Thus, cyanoacrylate can be a good substitute for silk sutures for wound closure in intraoral surgeries.
Keywords: cyanoacrylates; oral surgery; prospective studies; silk sutures; wound closure